Students' learning styles and thinking styles in science practical - Lee, Tze Jiun; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Science practical work is one of the ways to enhance students’ scientific knowledge and conceptual understandings through practical skills. The quality of students’ practical work in term of their ability to interpret, analyse and evaluate ideas and arguments is strongly dependent on the competency of a teacher who teaches science practical and also effectiveness of curriculum and instruction. In this concept paper will discuss overview of Social Learning Theory and Constructivist Theory that relevant to the need of learning science. The literature review will review about the important of learning style and thinking style that affect students’ learning in science practical.